2013
DOI: 10.1089/cyber.2012.0257
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Examination of Explanations for Reasons for Internet Nonuse

Abstract: Original citation:Helsper, Ellen J. and Reisdorf, Bianca C. (2013) This article investigates patterns of reasons for digital disengagement of British adults. It adds a psychological dimension to research that is mostly sociological in nature in trying to separate out explanations for disengaging from the Internet by choice or by forced exclusion. The analysis of a nationally representative survey shows differences between the number of reasons and the most important reasons among different sociodemographic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 15 publications
7
81
1
1
Order By: Relevance
“…More than a third (53/141, 37.6%) had previously attended a computer class and two-thirds (93/138, 67.4%) had asked someone else to use the Internet on their behalf. As all were responding to an offer of help with skills, we might assume (1) that they were interested in trying the Internet, perhaps again, and (2) that skills rather than lack of access or cost may be the main reason for current Internet nonuse [4]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a third (53/141, 37.6%) had previously attended a computer class and two-thirds (93/138, 67.4%) had asked someone else to use the Internet on their behalf. As all were responding to an offer of help with skills, we might assume (1) that they were interested in trying the Internet, perhaps again, and (2) that skills rather than lack of access or cost may be the main reason for current Internet nonuse [4]. …”
Section: Resultsmentioning
confidence: 99%
“…Helsper and Reisdorf [4] found that the oldest age group was more likely to indicate a lack of interest and skills as the reason for nonuse. Lack of interest in, or having no need for the Internet was also the main reason cited in 2013 by UK households [16] and in a Scottish study [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirmed that this level of disclosure was sufficient for achieving desirable outcomes while preserving user/group privacy. Our work also contributed to the scholarship of nonuse [3,9,17,25,29] as we detailed the needs of temporary non-use of smartphones and demonstrated a tool for supporting temporary non-use. Furthermore, NUGU design leveraged the key features of persuasive systems design, namely self-monitoring and social support [23].…”
Section: Discussionmentioning
confidence: 99%
“…While HCI literature mostly regards non-users as potential users who have not yet adopted the technology, increasing attention has been drawn to non-users in recent years, and researchers explored the sociocultural, socioeconomic, demographic, and other issues related to non-use [3,9,25,29]. Earlier studies attempted to categorize the diverse forms of non-use, which also significantly deepened our understanding about (non)users [25,29].…”
Section: Technology Non-usementioning
confidence: 99%
See 1 more Smart Citation